Meconium-stained liquor and its impact on maternal and neonatal outcome - Kashikar, Shweta; Kotpalliwar, Monika K.; Uttarwar, Pooja R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Meconium stained amniotic fluid (MSAF) is predictor of adverse fetal outcomes. However, all fetuses with meconium passage do not have an adverse outcome and it is important to distinguish those who develop fetal distress promptly to prevent and intervene the sequalae accordingly. Hence this study was undertaken to study the grades of meconium stained liquor and its effect on intrapartum management and relation with maternal and neonatal outcome. Methods: A prospective observational study was conducted on term pregnancy patients. Firstly, the detailed case history and examination was performed. When membranes ruptured the colour of liquor was noted. Fetal monitoring by cardiotocography (CTG) was done continuously throughout labour. The mode of delivery, cord pH and base excess were noted. After the delivery Apgar score and weight of the baby, need for resuscitation, neonatal intensive care unit (NICU) admissions and neonatal complications were noted. Results: Of the 3117 deliveries conducted during the study period, 321 cases (10.29%) had meconium stained liquor out of whom, 183 women (57%) were with thin meconium and 138 (43%) had thick meconium. There was no risk factor identified in the majority of women. The CTG was reactive in most women with thin meconium (71.5%). There was a significantly higher incidence of pathological CTG’s in women with thick meconium (36.3%) (p value = 0.001). There was no significant difference in birth weight Apgar scores, cord pH, base excess in both the groups and rate of NICU admission. Conclusions: Maximum patients with thin meconium and reactive CTG included in our study delivered normally with good neonatal outcome. However presence of thick meconium in addition to other factors such as fetal heart rate alterations should be viewed seriously as it may pose a potential danger for the baby.